Investigation of the ion exchange effect on surface properties and porous structure of clay: Application of ascorbic acid adsorption. Issue 5 (October 2019) - Anouar, Fatna; Elmchaouri, Abdellah; Taoufik, Nawal; Rakhila, Younes
Highlights: The cations exchange technique was used to improve chemical and physical Smectite properties at the modified state. The porosity was evaluated by BJH method, and a homogeneous distribution was found confirming the mesoporosity of Smectites. The modified Smectites was analyzed using XRD, FTIR, TGA and ICP-MS to highlight the modification process. The modified support was used as adsorbent for ascorbic acid elimination and the adsorption exhibits a heterogeneous surface. The presence of the acidic double band function in the FTIR analysis confirmed the ascorbic acid adsorption Absract: As part of the contribution to the synthesis and characterization of clay materials, fits the aim of this work. It is the improvement of some physical and chemical properties of Smectites between raw and modified state. The analyze of the exchanged cation effects on these properties include specific surface BET, external and internal surfaces, pore volume, pore size was determined by the nitrogen adsorption at 77 K and the experimental data were fitted by the isotherm adsorption models for gas. Clay purification and ion exchange are the most important treatment that expends a clay characteristic, more advanced than basic materials. As a result, higher adsorption is obtained for the sodium form of smectite this is associated with the intrinsic characteristics of the material. After the cation exchange, the specific surface area has increased from 210 to 440 m² g −1, the CEC reaches a value of 101 meq/100 g ditto for the pHpzc value which moved from neutral to basic pH. However, an overall decrease in the basal distance d001 was observed for NH4 + -SM and K + -SM. In the case of the Na + -SM, the d001 was slightly decreased. Moreover, the adsorption phenomena of ascorbic acid provides more information about the material surface. The four materials display a heterogeneous surface because the adsorption of ascorbic acid gets to the Freundlich model, also its kinetic fits the pseudo second order.